2020
DOI: 10.1186/s40798-020-00274-7
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Injuries in Soccer (Football): an Umbrella Review of Best Evidence Across the Epidemiological Framework for Prevention

Abstract: Soccer is the most popular sport in the world. Expectedly, the incidence of soccer-related injuries is high and these injuries exert a significant burden on individuals and families, including health and financial burdens, and on the socioeconomic and healthcare systems. Using established injury prevention frameworks, we present a concise synthesis of the most recent scientific evidence regarding injury rates, characteristics, mechanisms, risk and protective factors, interventions for prevention, and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 76 publications
3
59
0
Order By: Relevance
“…A match was defined as any friendly or competitive match. An injury was defined as one that occurs during a training session or match and prevents the player from performing the next training session or match [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A match was defined as any friendly or competitive match. An injury was defined as one that occurs during a training session or match and prevents the player from performing the next training session or match [39].…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence targets load (external and internal) management programs as an interesting tool to reduce injury risk among soccer players [39]. Moreover, considering the higher injury incidence rates during matches in male professional soccer players, Pfirrmann et al [40] recommended the review of those data in competition to reduce the overall injury rates.…”
Section: Introductionmentioning
confidence: 99%
“…The psychological and physical health benefits of physical activity and sports practice are well known and documented [ 3 , 4 , 5 , 6 ]. However, given its nature as a high-intensity contact sport, soccer is associated with a great injury risk, which makes it a target sport for injury prevention [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injury incidence among soccer players differs across levels of participation, age, type of exposure, and sex [ 1 , 8 , 15 , 16 , 17 ] with soccer players under the age of 12 years exhibiting a lower injury rate (1.0–1.6 injuries per 1000 h) compared to older players [ 1 , 16 , 17 ]. However, this rate varies considerably among different studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent umbrella review of best evidence for mitigating injury risk among soccer players, no single systematic or narrative review was found regarding intervention implementation and evaluation despite numerous systematic reviews and meta-analyses for studies regarding risk/protective factors and intervention efficacy. 6 Some of the challenges of capturing D&I in research can be addressed by clarifying core D&I concepts and principles to create a ‘common language’ for SEMS researchers and implementation partners and stakeholders, including policymakers, administrative leaders and practitioners in collaborative intervention efforts.…”
Section: Introductionmentioning
confidence: 99%